2011
DOI: 10.1007/s00712-011-0224-x
|View full text |Cite
|
Sign up to set email alerts
|

Friedman meets Becker and Mulligan in a monetary neoclassical growth model

Abstract: Friedman rule, Endogenous time preferences, Inflation tax, Neoclassical growth model, E22, E31,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This result is opposite to what is obtained under increasing marginal impatience. Chen, Hsu and Lu (2011), on the other hand, examined, in the presence of a cash-in-advance constraint, the effect of higher monetary growth rates on capital, consumption and welfare in the long-run, and reported that Friedman's money supply rule does not apply, and confirmed the existence of a mild positive optimal inflation rate.…”
Section: Discussionmentioning
confidence: 99%
“…This result is opposite to what is obtained under increasing marginal impatience. Chen, Hsu and Lu (2011), on the other hand, examined, in the presence of a cash-in-advance constraint, the effect of higher monetary growth rates on capital, consumption and welfare in the long-run, and reported that Friedman's money supply rule does not apply, and confirmed the existence of a mild positive optimal inflation rate.…”
Section: Discussionmentioning
confidence: 99%